Case–control study found that primary language disorders were associated with screen exposure. (18th December 2018) - Collet, M; Gagnière, B; Rousseau, C; Chapron, A; Fiquet, L; Certain, C
Abstract: Aim: We explored the associations between childhood exposure to screens, including televisions, computers, game consoles, tablets and smartphones and primary language disorders. Methods: This multi‐centre case–control study comprised 167 children aged 3.5–6.5 years, who were born in 2010–2012 and diagnosed with primary language disorders, and 109 matched controls without language disorders. Questionnaires were completed by their parents who were recruited by 16 family doctors and 27 speech and language therapists in the Ille‐et‐Vilaine region of France. The data were analysed using a multivariate logistic regression model and presented as adjusted odds ratios (aOR) and 95% confidence intervals (95% CI). Results: We found that cases (44.3%) and controls (22.0%) exposed to screens in the morning before nursery or primary school were three times more likely to develop primary language disorders (aOR 3.40, 95% CI 1.60–7.23). When this risk was combined with rarely or never discussing screen content with their parents (aOR 2.14, 95% CI 1.01–4.54) they were six times more likely to have language problems (aOR 5.86, 95% CI 1.44–23.95). Conclusion: Being exposed to screens in the morning before school, and rarely or never discussing screen content with parents, meant children were six times more likely to develop primary language disorders.